Morphometric studies on the embryonic gall bladder and cystic duct of Gaddi Sheep in different prenatal age groups (Journal of Applied and Natural Science, 2018)
The objective in the present study was to reconnoiter the morphological structure and biometrical parameters of embryonic gallbladder and cystic duct during the fetal life of Gaddi sheep. A Total number of 40 Gaddi sheep foetii samples were collected irrespective of sex and without any external anomaly or pathology. The age estimation of each foetus was done and accordingly the foetii were grouped as; group-I (1-60days), group-II (61-90days) groupIII (91-120days) and group-IV (121 –full term). The gall bladder from each foetii were excised hygienically. Gall bladder appeared at Crown Rump Length CRL 6.0 cm (46 days of gestationl age) and was slate blue colour in fresh state and settled into the visceral surface of right lobe of liver. It had single opening which continued as cystic duct. The maximum length and width of gall bladder (1.85 cm and 0.75 cm respectively) and cystic duct (1.68 cm and 0.18 cm respectively) increased with the advancement of gestational age.